Effects of management and co‐digestion on life cycle emissions and energy from anaerobic digestion. Issue 5 (7th May 2015) - Aguirre‐Villegas, Horacio A.; Larson, Rebecca; Reinemann, Douglas J.
Abstract: This study applies life cycle assessment (LCA) techniques to evaluate the processes controling the environmental impacts of anaerobic digestion (AD) pathways on a modeled dairy farm setting representative of Wisconsin. Seven electricity‐producing AD pathways are compared against a base‐case (BC) pathway to understand the effect of management practices, co‐digestion strategies, and energy conversion processes on greenhouse gas (GHG) emissions, ammonia (NH3 ) emissions, depletion of fossil fuels (DFF), and nutrient balances. The pathway selected has a substantial influence on the estimates of environmental impacts. GHG emissions range from 178 to 267 kg CO2 ‐eq GJ −1, NH3 emissions range from 11 to 18 kg GJ −1, DFF range from 176 to 327 MJ GJ −1, and N availability ranges from 7 to 15 kg GJ −1 of produced energy. The results of this paper show that the environmental benefits and concerns of anaerobic digestion systems can be further improved with the adoption of management practices on‐farm. Injection of digestate during land application is an effective management practice to reduce NH3 emissions, which at the same time increases N availability and reduces GHG emissions and DFF given that the manufacturing of purchased fertilizers is fossil energy intensive. Co‐digesting manure with corn stover and switchgrass increases energy production. Recovering heat has proven to be an easy to adopt strategy that improves all sustainability indicators without implementing major operational changes. Finally, 100 kg CO2 ‐eq GJ −1, 4.2 kg NH3 GJ −1 and 566 MJ GJ −1 are determined for GHG emissions, NH3 emissions and DFF respectively for a compressed biogas pathway. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd